Analyzing the Text of the Regulation on Quarantine During the COVID-19 Pandemic: Forensic Linguistic Study - Fithriyah Inda Nur Abida; I Wayan Pastika; Yunanfathur Rahman (Randwick International of Education and Linguistics Science Journal, 2022)
This study aims to analyze the text of the regulations on quarantine during pandemic COVID-19. Since Indonesia reported its first case of COVID-19 in the capital, Jakarta, in early March 2020, the pandemic has impacted all sectors of lives. With the fast spread of the COVID-19, the government mandates all sectors to take the necessary actions to prevent the spread. The enactment of Law Number 6 of 2018 concerning Health Quarantine then published which is then followed by various regional regulations both at the provincial and municipal levels. Descriptive qualitative method applied in this research. The data are the Regulation Number 67 of 2020 concerning the Implementation of Health Protocols in the Context of Prevention and Breaking the Chain of Spread of COVID-19 in the City of Surabaya followed by a Circular Letter Mayor of Surabaya Number 443 of 2021 concerning the Enforcement of Restrictions on Emergency Community Activities for COVID-19 in the City of Surabaya. The study found out that there was inconsistency between one article and another which tend to contradict and create ambiguity. This ambiguation leads to misunderstandings and allows violations of the rules